“Evaluación de la calidad físico-química y microbiológica de leche en centro de acopio del cantón Gonzanamá, Provincia de Loja” - Ochoa Caiza, Jeimy Solange (2025)
The quality of milk is an essential factor in ensuring its safety, nutritional value, and consumer acceptance. Physicochemical characteristics are fundamental for analyzing its authenticity and purity, while microbiological analyses assess product safety, as the presence of pathogens poses significant health risks. This study evaluated 54 milk samples from a collection center in the Gonzanamá canton, Loja province, analyzing physicochemical and microbiological parameters, the presence of antibiotic residues, and resistance. None of the samples fully complied with the NTE INEN 9 standard. Regarding antibiotic residues, sulfonamides were detected in 66.67% of the samples and tetracyclines in 12.96%. Microbiologically, a high prevalence of Staphylococcus aureus (31%) and Escherichia coli (11%) was identified. Antimicrobial resistance was observed in Staphylococcus aureus against antibiotics such as aztreonam (79%), amoxicillin + clavulanic acid (76%), tetracycline (70%), sulfamethoxazole + trimethoprim (60%), and oxacillin (58%). Additionally, Escherichia coli showed 36% resistance to amoxicillin + clavulanic acid. The results indicate quality and safety issues in the raw milk produced in Gonzanamá, particularly due to water adulteration, the presence of antibiotic residues, pathogenic microorganisms, and resistance factors. It is recommended to implement better milking practices, hygienic handling, and milk preservation, as well as periodic controls to ensure a quality product for human consumption.